The Direct Method In Arabic Language Teaching: A Theoretical Study And Its Relevance In The Modern Era - Fathul Abrar Azzahra (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
The learning of Arabic is often perceived as a challenging process, particularly for learners who do not have a background as native speakers. This study aims to examine in depth the concept of the direct method and to understand its implementation in Arabic language learning. This study employs a qualitative-descriptive approach using library research as the primary framework for examining the issues, with data collected from both primary and secondary sources and subsequently analysed critically to reveal patterns, conceptual relationships, and contributions to the development of understanding regarding Arabic language teaching methods. This approach places emphasis on the development of speaking and listening skills as the primary foundation for language mastery; furthermore, the direct method emphasises the intensive use of Arabic during the learning process, so that vocabulary and grammatical structures are introduced gradually and naturally through interactions occurring during the learning process. As a result, learners do not merely gain a theoretical understanding of the structure and forms of the language, but are also trained to use it communicatively. This approach encourages them to interact in a variety of more realistic and contextual situations, thereby enabling their language skills to develop in a more natural and functional way.